Analysis of Current Infrastructure and Emerging Trends of Information and Communication Technology in the Indian Himalayan Region - Rakesh Kumar Singh (International Journal of Engineering and Management Research, 2019)
In this era of growing technologies, the internet and the information and communication technologies are not only the precursor of communication architecture but it is also the technology of production and social organisation, which has a pivot role in redesigning the social, economical, public and political aspects. Today, the term information technology incorporates many aspects of computing and technology like software applications, computer networks and information databases. When the computer and the communication are combined then it becomes the ICT. Presently, ICT infrastructure in the IHR is not in a good condition but nowadays, various new ICT technologies are emerging day by day through which ICT infrastructure could be upgraded in the remote areas of the IHR. ICT can play a significant role in development of the IHR and its peoples trough communication and internet technologies.